Comprehensive Hazard Identification and Risk Assessment (HIRARC) in the Coffee Production Process: A Case Study of Kopi Lanange Jagad - _ Hidayat; Mochammad Nuruddin; Elly Ismiyah; Said Salim Dahda; Nina Aini Mahbubah; Rifky Maulana Yusron; Rohmat -; Muhammad Zainur Ridlo (International Journal of Science, Engineering, and Information Technology, 2025)
Occupational Safety and Health (OSH) plays a critical role in maintaining safe and sustainable production, particularly in small-scale agro-industrial operations such as coffee processing. This study applies the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) framework to evaluate workplace hazards at Kopi Lanange Jagad, a micro-scale coffee producer in Malang Regency, Indonesia. Field observations and structured interviews were conducted to identify potential hazards across four production stages roasting, grinding, sieving, and packaging. Quantitative measurements were also taken, including ambient temperature, noise level, and airborne dust concentration, to provide empirical data for risk evaluation. The findings identified a total of 12 hazards, classified into three risk categories: high (25%), moderate (50%), and low (25%). The roasting process exhibited the highest risk score (R = 18.4), with average workplace temperatures reaching 85°C–120°C, significantly exceeding the national occupational limit of 30°C for moderate workloads (Permenaker No. 5/2018). The grinding stage also presented considerable hazards, with airborne dust concentrations averaging 2.4 mg/m³, approaching the Ministry of Manpower’s threshold limit value (TLV) of 3 mg/m³. Manual packaging was associated with ergonomic strain, where workers lifted 15–20 kg sacks repeatedly, leading to potential musculoskeletal disorders. Risk evaluation revealed that existing control measures such as natural ventilation and sporadic use of personal protective equipment (PPE) were insufficient to ensure worker safety. To reduce these hazards, the study recommends implementing engineering controls such as local exhaust ventilation and machine insulation, combined with administrative measures including job rotation, scheduled rest breaks, and regular safety training. Ensuring consistent PPE use especially heat-resistant gloves, dust masks, and ear protection can further mitigate residual risks. Overall, the application of the HIRARC framework at Kopi Lanange Jagad demonstrates its effectiveness as a low-cost and practical tool for identifying, prioritizing, and managing occupational hazards in small-scale coffee industries. Implementation of the proposed control strategies is projected to reduce total workplace risk by 35–40%, improving both worker well-being and operational productivity.